Frequent experience of discrimination among people who inject drugs: Links with health and wellbeing - Couto e Cruz, C.; Salom, C.; Dietze, P.; Lenton, Simon; Burns, L.; Alati, Rosa (Elsevier Ireland Ltd, 2018)
© 2018 Elsevier B.V. Background: Previous research has shown that people who inject drugs (PWID) experience discrimination on a regular basis. This study explores the relationships between discrimination against PWID and health and wellbeing. Methods: Data on discrimination against PWID and their health and wellbeing were drawn from the Illicit Drug Reporting System collected in Australia in 2016. The Personal Wellbeing Index was used to measure wellbeing, and the Kessler-10 scale was used to measure psychological distress. Experience of overdose, injecting related illnesses, diseases, and risky injecting behaviour were also assessed. We fitted multivariate logistic regression models adjusted for socio-demographic, imprisonment history, and drug-related factors. Results: Of the 796 participants included in the study, the majority who reported experiencing discrimination were male (65%), heterosexual (89%), and unemployed (89%). Thirty percent of the sample (n = 238) reported they had never experienced discrimination because of their injecting drug use. Seventeen percent of participants had not experienced discrimination in the twelve months prior to the interview, 24% experienced discrimination monthly, 16% experienced discrimination weekly, and 13% experienced discrimination daily or more. Frequent discrimination was associated with increased odds of overdosing, injecting related illnesses and diseases, mental health issues, and poor wellbeing. Among those who reported experiencing discrimination, females and those who identified as Indigenous were found to have poorer health and wellbeing outcomes. Conclusions: Our findings highlighted that frequent discrimination may lead to worse health and wellbeing among PWID. If our findings are supported by other research, policies aimed at reducing discrimination against PWID may be warranted or improved.